3D Clay Printing: A Taguchi Approach To Rheological Properties And Printability Assessment - Rihani Nadir; Oulkhir Fatima-Zahra; Igwe Nnamdi C.; Akhrif Iatimad; El Jai Mostapha (E3S Web of Conferences)
In the general context of 3D clay printing and sustainable mix design, reaching optimal printing quality and structural integrity requires a thorough understanding of the fresh paste and solid properties of earthen materials. This study investigates the rheology of Benjellik clay using Taguchi Design plan, focusing on the effects of particle size and water content on the related fresh paste properties. A set of nine clay formulations were analysed in terms of yield stress, plastic viscosity, consistency, and flow number according to both Bingham and Bulkley models. Results revealed that water to binder ratio (W/B) mainly impacts rheological properties; it reduces yield stress and plastic viscosity while increasing the flow number. Moreover, the pre-selected raw particle sizes had irrelevant impact due to similarities of the related statistical distributions as corroborated by laser granulometry tests. Furthermore, optimal layer heights to nozzle diameter ratio was found to be around 0.55 enhancing the material flowability and scanned tracks features. Finally, the findings emphasize the crucial role of W/B along with the layer height to nozzle size ratios in stabilizing the printability of clay materials, offering a confident printing parameters area for optimizing both 3D printing clay of Fez region of Morocco.